Carbohydrate and fat have different effects on plasma leptin concentrations and adipose tissue leptin production. - Evans, K; Clark, M; Frayn, K (2001)
Leptin is secreted by adipocytes and plays a role in the regulation of food intake. However, the regulation of leptin production by adipose tissue is unclear. We have investigated whether a mixed meal or a high-fat load given orally, or a pure fat load given intravenously, stimulates adipose tissue leptin production. Six volunteers were studied on two occasions following an overnight fast. On one occasion they consumed tomato soup containing 40 g of triacylglycerol (as Intralipid) and 9.6 g of carbohydrate; on the other occasion Intralipid was infused intravenously over 4 h to give the same fat load. A further eight subjects consumed a mixed meal (containing 37 g of fat and 100 g of carbohydrate) after an overnight fast. Paired blood samples were obtained from an arterialized hand vein and a vein draining subcutaneous adipose tissue at baseline and for 6 h following the meals or the start of the infusion. After both the intravenous and oral fat loads, the arterialized and adipose venous plasma leptin concentrations decreased over 6 h (both P<0.001), as did the leptin veno--arterial difference (P=0.01). Following the mixed meal, there was a slight increase in the arterialized plasma leptin concentration (P=0.02) and a more marked increase in the adipose venous plasma leptin concentration (P=0.03) and in the adipose tissue leptin veno--arterial difference (P=0.01), all peaking at 240 min. We conclude that the increase in plasma leptin concentration observed after meals is not simply a result of an energy load, but is in response to a signal that is not present following a fat load without carbohydrate.